Disruption of hyaluronan synthase-2 abrogates normal cardiac morphogenesis and hyaluronan-mediated transformation of epithelium to mesenchyme - Camenisch, Todd D. (American Society for Clinical Investigation, 2000)
We identified hyaluronan synthase-2 (Has2) as a likely source of hyaluronan (HA) during embryonic development, and we used gene targeting to study its function in vivo. Has2(–/–) embryos lack HA, exhibit severe cardiac and vascular abnormalities, and die during midgestation (E9.5–10). Heart explants from Has2(–/–) embryos lack the characteristic transformation of cardiac endothelial cells into mesenchyme, an essential developmental event that depends on receptor-mediated intracellular signaling. This defect is reproduced by expression of a dominant-negative Ras in wild-type heart explants, and is reversed in Has2(–/–) explants by gene rescue, by administering exogenous HA, or by expressing activated Ras. Conversely, transformation in Has2(–/–) explants mediated by exogenous HA is inhibited by dominant-negative Ras. Collectively, our results demonstrate the importance of HA in mammalian embryogenesis and the pivotal role of Has2 during mammalian development. They also reveal a previously unrecognized pathway for cell migration and invasion that is HA-dependent and involves Ras activation.